EXperienceS and aTtitudes towards Agitated behaviours in Traumatic brain injury in the Intensive Care unit patients (EXSTATIC): a protocol for an interprofessional mixed-method study. Issue 7 (14th July 2021) - Saavedra-Mitjans, Mar; David, Pierre-Marie; Frenette, Anne-Julie; Arbour, Caroline; Perreault, Marc; Williams, Virginie; Bernard, Francis; Williamson, David
Abstract : Introduction: Agitation and violent behaviours are common conditions developed by patients with acute traumatic brain injury (TBI) in intensive care units (ICUs). Healthcare professionals caring for these patients have various tools to manage these behaviours, but lack of a formal protocol to assess and manage them makes caring for these patients a challenge. Moreover, safety may often be compromised for both ICU professionals and patients encountering such situations. The EXperienceS and aTtitudes towards Agitated behaviours in Traumatic brain injury in the Intensive Care unit patients (EXSTATIC) study aims to explore the experiences and attitudes of ICU nurses and other ICU healthcare professionals on the management of agitated behaviours in patients with acute TBI. Methods and analysis: EXSTATIC is a multicenter mixed methods convergent study exploring experiences and attitudes of ICU healthcare professionals caring of agitated patients with TBI. The study includes three qualitative methods (observation, semistructured interviews and focus groups) and one quantitative method (retrospective cohort). The integration of the different methods will be done using sequential steps of the research and by the integration of results for each step. Qualitative data will be evaluated following a thematic analysis derived from a grounded theory approach. Quantitative data will be analysed using descriptive statistics. Qualitative and quantitative results will be combined in a convergent interactive interpretative design. Gender and race perspective will be integrated in collection, analysis and interpretation of data. Ethics and dissemination: This study has been approved by the Centre intégré universitaire de santé et de services sociaux du nord de l'île de Montréal (CIUSSS-NÎM) Research Ethics Board. The findings will be disseminated locally with ICU staff and health managers, international peer-reviewed journals, a PhD dissertation, and national and international conferences. The knowledge derived from this study is key in the development of clinical protocols to manage agitation and related behaviours in patients with TBI and designing further interventional studies targeting this specific problematic. Trial registration number: NCT04741399 .